2015
DOI: 10.4103/2347-9264.169494
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of one-stage versus two-stage breast reconstruction in the United Kingdom

Abstract: of a saline implant and permit long-term, noninvasive adjustment of breast size. Reconstruction can, therefore, be completed as a single procedure. The implant is placed at the index procedure, expansion achieved with repeat outpatient injections of saline until optimum breast size is reached. The traditional two-stage reconstruction, however, involves two operations, the first involving the , at a mean of 12.9 months postimplantation, the majority of which were exchanged for silicone implants to improve cosme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The base case risk of reconstruction failure (8.6 per cent) was drawn from a large study across many centres in the UK 11 . The target rate according to breast reconstruction guidelines in the UK 26 is less than 5 per cent, and the recent study 12 from which the effectiveness of sNPWT was taken recorded a rate of around 4 per cent. Sensitivity analyses were therefore included based on these rates in addition to one-way analyses and a probabilistic model.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The base case risk of reconstruction failure (8.6 per cent) was drawn from a large study across many centres in the UK 11 . The target rate according to breast reconstruction guidelines in the UK 26 is less than 5 per cent, and the recent study 12 from which the effectiveness of sNPWT was taken recorded a rate of around 4 per cent. Sensitivity analyses were therefore included based on these rates in addition to one-way analyses and a probabilistic model.…”
Section: Discussionmentioning
confidence: 98%
“…This evaluation has limitations. The effectiveness of sNPWT was based on a comparative study 12 that was not randomized. The authors 12 concluded that sNPWT should be considered at the surgeon’s discretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations